Isolation and characterisation of potential probiotic yeast strains from local fermented foods : Gastrointestinal tolerance and antimicrobial activity assessment - Amirul Syafiq, Murad; Nur Ain, Zuhairi; Mohd Amir Shahlan, Mohd Aspar; Mohd Akmal, Azhar (University of Malaya, 2024)
Probiotic microorganisms, offering health benefits when consumed in sufficient quantities, are gaining recognition for their potential role in promoting wellness. This study focuses on isolating and characterising potential probiotic yeast strains sourced from fermented food products. This research evaluates the gastrointestinal tolerance and antimicrobial activity of isolated yeast strains, with the potential application in probiotic supplements and functional foods. Yeast strains were isolated from fermented food sources and identified using morphological analysis, PCR, gene sequencing, and genetic identification. Gastrointestinal tolerance was assessed through simulated gastric fluid (SGF) exposure, and antimicrobial activity was tested against foodborne pathogens. Six yeast strains (Diutina mesorugosa, Pichia kudriavzevii, Candida mesorugosa, Candida sp) were identified. They exhibited varying resistance to low pH in SGF, suggesting survivability in the stomach. Some strains selectively inhibited specific Gram-negative pathogens like Pseudomonas aeruginosa and Salmonella sp. These findings suggest the isolated yeast strains may serve as probiotics, promoting digestive health and food safety. They are potentially used in probiotic supplements and functional foods, promising improved overall well-being.